2011
DOI: 10.1097/pcc.0b013e3181e2a53b
|View full text |Cite
|
Sign up to set email alerts
|

A clinic-biological score for diagnosing early-onset neonatal infection in critically ill preterm infants*

Abstract: A predictive model combining serum IL-6 and IL-8 measurements and selected clinical variables could distinguish infected from noninfected preterm infants at birth and should help the clinician in reducing or shortening the unnecessary use of antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…In contrast to these findings Jung et al ( 38 ), pointing to the fact that LOS has been observed in infants born with FIRS after an initial period of clinical improvement, suggested that the anti-inflammatory response might play an important role in the development of LOS. Increased concentrations of anti-inflammatory cytokines like IL-10 measured in infected infants ( 42 , 49 ) proof the activation of an anti-inflammatory immune response and support this theory ( 38 ).…”
Section: Diagnosis Of Neonatal Sepsismentioning
confidence: 79%
See 1 more Smart Citation
“…In contrast to these findings Jung et al ( 38 ), pointing to the fact that LOS has been observed in infants born with FIRS after an initial period of clinical improvement, suggested that the anti-inflammatory response might play an important role in the development of LOS. Increased concentrations of anti-inflammatory cytokines like IL-10 measured in infected infants ( 42 , 49 ) proof the activation of an anti-inflammatory immune response and support this theory ( 38 ).…”
Section: Diagnosis Of Neonatal Sepsismentioning
confidence: 79%
“…None of the widespread laboratory markers of infection [C reactive protein (CRP), white blood cell count (WBC), absolute neutrophil count (ANC), immature to total neutrophil ratio (IT-ratio)] has enough sensitivity or specificity to detect all infected children ( 17 , 49 ). Their diagnostic value might be especially limited in the early course of the disease ( 49 ). CRP, for example, is known to rise not earlier than 12–24 h after the onset of neonatal infection ( 2 ).…”
Section: Diagnosis Of Neonatal Sepsismentioning
confidence: 99%
“…We found 19 articles which were eligible for inclusion in our review [61,[70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87]. Papers were published between 1995 and 2014.…”
Section: Methodological Quality Of the Included Studiesmentioning
confidence: 99%
“…In view of the latest advances in neonatal care, these reference intervals derived from only 35 near-term and 113 term newborns need additional refinement in a larger sample of healthy neonates including, in particular, those born before 35 weeks of gestation, that is, those that now populate most NICUs [61]. term used was: (Interleukin-6 OR IL-6) AND (neonatal sepsis OR neonatal infection OR sepsis).…”
Section: Il-6 Reference Intervals and Dynamics In The Early Postnatalmentioning
confidence: 99%
“…During full‐text screening, 48 publications were excluded because of: theoretical research, lack of clinical outcomes, and duplicate articles . Therefore, a final total of 31 studies were used for the current meta‐analysis, of which 1448 neonates were studied and evaluated in the sepsis group and 1628 neonates in the no‐sepsis group (see Figure ). Table shows the major characteristics of the selected studies.…”
Section: Resultsmentioning
confidence: 99%